Social variation Of malay language In Kuching, Sarawak, Malaysia:A study on accent, identity and integration - Idris Aman; Rosniah Mustaffa (Pernerbitan UKM, 2009)
Language variation is conveyed through its regional or social dimension. In line with that proposition, this paper discusses the social variation of Malay language spoken in Kuching, Sarawak, Malaysia focussing on their accents. As part of the Malay language society, the Malays of Kuching have their own accent which is different from other Malay accents or the standard national accent. This paper analyzes the status of national standard accent and non-standard accent among the Malay informants in the city of Kuching. The discussion is based on a sociological urban dialectology research. For the analysis, five phonological variables are chosen. They are open-ended vowels (a), such as kita ‘we’, close-ended (i), such bilik ‘room’, close-ended (u), such as masuk ‘enter’, initial (r) or (r)1, such as rumah ‘home’, and final (r) or (r)2, such as pasar ‘market’. Issues on accents are studied through four different degree of formality of speech styles, namely reading word list style (WLS), reading passage style (PS), conversational style (CS) and story-telling style (STS). Three social contextual variables - socio-economic status, sex, and age groups of the informants will be considered in the analysis. The use of national standard accent compared with the non-standard accent will be linked to issues of identity and integration